2010
DOI: 10.1002/nur.20399
|View full text |Cite
|
Sign up to set email alerts
|

Patient falls: Association with hospital Magnet status and nursing unit staffing

Abstract: Abstract:The relationships between hospital Magnet 1 status, nursing unit staffing, and patient falls were examined in a cross-sectional study using 2004 National Database of Nursing Quality Indicators (NDNQI 1 ) data from 5,388 units in 108 Magnet and 528 non-Magnet hospitals. In multivariate models, the fall rate was 5% lower in Magnet than non-Magnet hospitals. An additional registered nurse (RN) hour per patient day was associated with a 3% lower fall rate in ICUs. An additional licensed practical nurse (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
155
6
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 20 publications
16
155
6
12
Order By: Relevance
“…Patient falls in hospitals are common and affect approximately 2% to 17% of patients during their hospital stay [3][4][5][6][7]. Fall related injuries occur in 15% to 50% of the patients, including major injuries such as fractures or lacerations in 1% to 10% [7][8][9][10]. Furthermore, falls may lead to fear of falling with subsequent activity restriction, prolonged hospital stay and legal liability [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient falls in hospitals are common and affect approximately 2% to 17% of patients during their hospital stay [3][4][5][6][7]. Fall related injuries occur in 15% to 50% of the patients, including major injuries such as fractures or lacerations in 1% to 10% [7][8][9][10]. Furthermore, falls may lead to fear of falling with subsequent activity restriction, prolonged hospital stay and legal liability [11].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently the utilization of fall risk assessment tools to evaluate patients' risks for falls apparently are not effectively reducing inpatient fall rates because of human factors and ergonomics in a hospital environment [2]. Patient falls in hospitals are common and affect approximately 2% to 17% of patients during their hospital stay [3][4][5][6][7]. Fall related injuries occur in 15% to 50% of the patients, including major injuries such as fractures or lacerations in 1% to 10% [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have not been able to demonstrate a benefit of Magnet status. [12][13][14] On the contrary, others have identified superior outcomes for Magnet facilities in falls, 27 general trauma, 28 and neonatal care. 29 For elderly surgical patients, Friese et al 10 demonstrated that hospitalization in a Magnet hospital was associated with decreased 30-d mortality and rates of failure to rescue.…”
Section: Discussionmentioning
confidence: 99%
“…The perspective of those who render the service should draw the attention of researchers concerned about patient safety. 3 Aligned with these thoughts, some studies show a growing number of nurses committed to the creation of safer systems, taking over leading positions toward providing patients with risk-free quality care. 4 In Uruguay, authorities are constantly concerned about the safety of patients.…”
Section: Introductionmentioning
confidence: 99%